2021
DOI: 10.2337/dc21-0490
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Model–Derived Insulin Sensitivity Index Underestimates Insulin Sensitivity in Black Americans

Abstract: OBJECTIVE To examine the ethnic differences in insulin sensitivity (S I ) as measured by the minimal model approach (S I -MM) and the reference method, the euglycemic-hyperinsulinemic clamp (EHC). RESEARCH DESIGN AND METHODS In a prospective study design, thirty Black Americans (BA) were age, sex, and BMI matched with non-Hispanic Whites (NHW). Participants underwent frequently sampled intravenous tolerance test (FSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Additional studies have evaluated insulin sensitivity in AA individuals and NHW individuals by using the hyperinsulinemic-euglycemic clamp procedure without concomitant glucose tracer infusion (9,11,30). This approach evaluates predominantly insulin-stimulated glucose disposal and demonstrated no difference in insulin sensitivity between AA individuals and NHW individuals (9,11,30). These findings are consistent with the results from our study but are in stark contrast to the results from the majority of studies that have evaluated the effect of race on insulin sensitivity by using an IVGTT in conjunction with minimal model analysis and found that AA individuals are more insulin resistant than NHW individuals (5,14,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have evaluated insulin sensitivity in AA individuals and NHW individuals by using the hyperinsulinemic-euglycemic clamp procedure without concomitant glucose tracer infusion (9,11,30). This approach evaluates predominantly insulin-stimulated glucose disposal and demonstrated no difference in insulin sensitivity between AA individuals and NHW individuals (9,11,30). These findings are consistent with the results from our study but are in stark contrast to the results from the majority of studies that have evaluated the effect of race on insulin sensitivity by using an IVGTT in conjunction with minimal model analysis and found that AA individuals are more insulin resistant than NHW individuals (5,14,31).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma insulin concentration during the OGTT was numerically also about 10% lower in the AA group than in the NHW group, but the plasma insulin concentration AUC 0-120 was not statistically significantly different between the two groups (Figure2C,D).ISR AUC 0-120 (Figure2E,F) and hepatic insulin delivery AUC 0-120 (Figure2G,H) during the OGTT were about 20% less (p < 0.05 and p = 0.06, respectively) in the AA group than in the NHW group. The difference in ISR between the two groups was due to the difference in plasma glucose concentration because ISR in relationship to plasma glucose concentration, assessed as either the ISR AUC 0-120to-plasma glucose concentration AUC 0-120 ratio (138[11] and 156[8] pmol/mM), the ISR iAUC 0-120 -to-plasma glucose concentration iAUC 0-120 ratio (355[218, 419] and 340[235, 423] pmol/mM, respectively), or the ISR in relation to plasma glucose concentration at each time point during the OGTT (Figure2I), was not different between the two groups. Plasma ICR was numerically ~10% less in the AA group than in the NHW group, but the difference did not reach statistical significance (Figure2J).Insulin kinetics during the insulin-modified IVGTTIn a subset of the participants (NHW participants: n = 11; AA participants: n = 7), insulin kinetics were also assessed using an IVGTT.…”
mentioning
confidence: 99%
“…This study suggested a higher preponderance of Black in the positive correlation between METS-IR and serum ferritin. Previous studies have shown that Black Americans are less sensitive to insulin and have a higher risk of insulin resistance compared to non-Hispanic whites ( 28 , 29 ). In participants with unknown exact ethnicity information, we found a non-linear relationship between METS-IR and serum ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] A minimal model analysis of the FSIGT data was used to estimate the indices of glucose effectiveness (S g ) and insulin sensitivity (S i ) as previously described using MIN-MOD software (version 6.02) (MINMOD Millennium). 15 AIR g is calculated as the area under the curve (AUC) for first phase insulin secretion between 0 and 10 min. The disposition index was calculated as the product of S i multiplied by AIR g .…”
Section: Data and Statistical Analysesmentioning
confidence: 99%